Climate Smart Coffee in El Salvador - Fernández Kolb, Pablo; Castro-Llanos, Fabio Alexander; Martínez Valle, Armando Isaac; Siles, Pablo; Läderach, Peter R.D.; Lundy, Mark M.; Bunn, Christian (International Center for Tropical Agriculture, 2019)
Coffee is a staple of Central American exports and agricultural production, not least in El Salvador. Coffee is the second-highest export in terms of value at around US$ 113.4 million in annual foreign currency earnings. The coffee sector directly generates over 40,000 jobs in rural El Salvador. El Salvador exclusively produces high-quality Arabica coffee, cultivated mostly at an altitude ranging between 600 to 900 masl (51%). These features set the future of coffee farming in El Salvador on an increasingly narrow and uneven path. In contrast to Robusta, the Arabica variety is highly vulnerable to climate change, especially at the low altitude at which it is mainly grown in El Salvador. To aggravate this situation, studies show that Mesoamerica, and El Salvador in particular, is the region projected to endure the most severe impacts of increasing temperatures on Arabica production. The climate-smart agriculture (CSA) concept reflects an ambition to improve the integration of agriculture development and climate responsiveness. It aims to achieve food security and broader development goals under a changing climate and increasing food demand. CSA initiatives sustainably increase productivity, enhance resilience, and reduce/remove greenhouse gases (GHGs). While the concept is new and still evolving, many of the practices that make up CSA already exist worldwide and are used by farmers to cope with various production risks. Mainstreaming Climate Smart Coffee (CSC) requires critical stocktaking of the sector fundamentals, already evident and projected climatic developments relevant to coffee production and promising practices for the future, and of institutional and financial enablers for CSC adoption. This CSC profile provides a snapshot of a developing baseline created to initiate discussion, both within countries and globally, about entry points for investing in CSC at scale.